INVESTMENTS IN TECHNOLOGICAL INNOVATIONS: A LITERATURE REVIEW OF ORGANIZATION DETERMINANTS - Radu, Laura-Diana (European Scientific Journal, ESJ, 2015)
The study of a complex phenomenon such as innovation requires different levels of interdisciplinary analysis. Assuming that the enterprise is the fundamental agent of economic change, this paper aims to analyse the literature in the field of technological innovation and determinants that stimulate organizations to engage in innovative process. The technological innovation is an instrumental factor in creating new forms of value in such a competitive environment as the current economic, social and politic world is. It favours the creation of new products which are accepted and sold worldwide, with a competitive price and quality. The technological innovation should be supported both by the public and the business enterprise expenditure. Results of the innovative process depend not only on product or process obtained, but also of its efficient management. Companies’ managers should cultivate a pro-innovation attitude inside also in their relations with the outside world and to stimulate employees and collaborators by offering various incentives and create a favourable environment for shaping innovative ideas which on longer or shorter term could bring financial and / or competition benefits.